WORD OF MOUTH RELATIONSHIP ANALYSIS ON PURCHASE INTENTION AND ITS IMPACT ON PURCHASE DECISIONS - Dicky Apdillah; Riyan Fiqri Hidayat; Chairanda Al Azmi; Ahmad Zuwandana (Transpublika Publisher, 2022)
This study aims to analyze the relationship of Word of Mouth in Purchase Intention toward Purchase Decision. This study is a quantitative study using SEM PLS. The sample in this study was 100 respondents to consumers of Alfamart Kramat Pulo 2 with a non-probability sampling technique, namely a sampling technique that provides equal opportunities for each element (member) of the population to be selected as a member of the sample. The data the analyzed using validity test and hypothesis test to obtain the result. The finding reveals that by empirical analysis, word of mouth has a statistically significant positive impact on purchasing interest, such that as word of mouth improves, so does purchasing intention. Meanwhile, in empirical evidence, purchasing intention has a positive and significant impact on purchasing decisions, such that if the purchasing interest in a product becomes increasingly attached to the minds of customers, the likelihood of making a purchase increases. Furthermore, according to empirical research, word of mouth has a positive and statistically significant impact on purchasing decisions.